2022
DOI: 10.3389/fmicb.2022.1024702
|View full text |Cite
|
Sign up to set email alerts
|

The combination effect of meropenem/sulbactam/polymyxin-B on the pharmacodynamic parameters for mutant selection windows against carbapenem-resistant Acinetobacter baumannii

Abstract: The objective of this study was to evaluate whether combinations of sulbactam, meropenem, and polymyxin-B could reduce or close the gap of mutant selection window (MSW) of individual antibiotics against Acinetobacter baumannii harboring OXA-23. MICs of three antimicrobials used alone and in combination (meropenem/polymyxin-B or meropenem/polymyxin-B/sulbactam) were obtained in 11 clinical isolates and mutant prevention concentrations were determined in 4 of the 11 isolates. All isolates were resistant to merop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 55 publications
1
4
0
Order By: Relevance
“…The Figs show that accurate bell-shaped relationships fitted with Gaussian function were observed. Similar bell-shaped "PK/PD index-resistance" relationships were previously reported in several studies with non-beta-lactam antibiotics with an account of the mutant selection window (MSW) hypothesis [10][11][12][13][14][15][16][17]; in this regard, beta-lactam antibiotics were not well described. Interestingly, despite meropenem degradation throughout time-kill experiments and the resultant pharmacokinetic profiles that differed significantly from targets, T MSW values, calculated with desired meropenem concentrations, were consistent with the enrichment of the bacterial population with resistant cells.…”
Section: Plos Onesupporting
confidence: 74%
See 1 more Smart Citation
“…The Figs show that accurate bell-shaped relationships fitted with Gaussian function were observed. Similar bell-shaped "PK/PD index-resistance" relationships were previously reported in several studies with non-beta-lactam antibiotics with an account of the mutant selection window (MSW) hypothesis [10][11][12][13][14][15][16][17]; in this regard, beta-lactam antibiotics were not well described. Interestingly, despite meropenem degradation throughout time-kill experiments and the resultant pharmacokinetic profiles that differed significantly from targets, T MSW values, calculated with desired meropenem concentrations, were consistent with the enrichment of the bacterial population with resistant cells.…”
Section: Plos Onesupporting
confidence: 74%
“…To address these issues we tested the well-known mutant selection window hypothesis with meropenem. The mutant selection window (MSW) hypothesis is applicable [10] to explain resistance patterns of several classes of antibiotics [11][12][13][14][15][16][17]; however, only a few such studies have been reported with beta-lactams [12,17].…”
Section: Introductionmentioning
confidence: 99%
“…Our previous study demonstrated the synergistic effect of another triple-combination therapy consisting of polymyxin-B/ meropenm/sulbactam (Menegucci et al, 2019;Fedrigo et al, 2021;Zhang et al, 2022;Zhu et al, 2022b) and demonstrated disruption of the metabolomic profile of a clinical A. baumannii isolate (Zhu et al, 2022c). The metabolites involved in the cell wall synthesis, outer membrane integrity and central carbon metabolism were primarily affected by polymyxin-B/meropenem or polymyxin-B/ meropenem/sulbactam combinations.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the present study replaced meropenem with amikacin; this triple-antibiotic combination with amikacin also disrupted metabolisms of the nucleotides, amino acids and peptides. There is a stark difference in treatment effects for the two triple-antibiotic combinations that may explain why the combination with amikacin resulted in a better bactericidal effect and inhibition of mutant selection for their clinical regimens based on model-simulated parameters ( Zhang et al, 2022 ; Zhu et al, 2022a ).…”
Section: Discussionmentioning
confidence: 99%
“…Coadministration of 2 or more antibiotics is a potential solution to the global problem of limited antibiotic monotherapy options against these multidrug-resistant bacteria. [7][8][9][10][11] Ceftaroline is a fifth-generation cephalosporin with in vitro and in vivo MRSA activities for the treatment of bacterial skin and skin structure infections. 12,13 There are clinical and experimental evidences showing that β-lactams and cationic antimicrobial peptides have synergistic activities and can sensitize innate host defence to decrease the virulence of the pathogen.…”
mentioning
confidence: 99%